Ethnomathematics in ten Indonesian traditional musical instruments - Heru Sukoco; Yohana Sinta Kristyasari (Ethnomathematics Journal, 2022)
This article aimed to describe the results of the ethnomathematical exploration of traditional musical instruments that can be used as mathematics teaching materials. The research method chosen in this study was the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret available research with areas and topics of interest. Data collection is done by documenting and reviewing all articles related to ethnomathematics on traditional musical instruments, selecting only those using Indonesian traditional instruments, and publishing them in Indonesian national journals. It was found that 10 articles matched these criteria. The results showed that ethnomathematics-based mathematics learning on traditional musical instruments can be used in the learning process and can be used as a learning resource, a means of introducing mathematics through culture, implemented in mathematics learning, and as teaching materials in learning mathematics. The uses in learning can be the shapes of the instruments as well as how to play the instruments that yield number patterns.